Milk protein digestion and the gut microbiome influence gastrointestinal discomfort after cow milk consumption in healthy subjects - Tagliamonte, Silvia; Barone Lumaga, Roberta; De Filippis, Francesca; Valentino, Vincenzo; Ferracane, Rosalia; Guerville, Mathilde; Gandolfi, Ivana; Barbara, Giovanni; Ercolini, Danilo; Vitaglione, Paola (Food research international, 2023)
[Display omitted] •Thirty-one bioactive peptides from milk digestion are identified in human plasma.•Subjects with gastrointestinal discomfort show lower circulating bioactive peptides.•Plasma peptides opioid agonists and antagonists affect gastrointestinal discomfort.•Milk derived-DPPIV inhibitors in plasma affect serum DPPIV activity.•Gut microbiome proteolytic activity may affect gastrointestinal discomfort. Many healthy people suffer from milk-related gastrointestinal discomfort (GID) despite not being lactose intolerant; the mechanisms underpinning such condition are unknown. This study aimed to explore milk protein digestion and related physiological responses (primary outcome), gut microbiome and gut permeability in 19 lactose-tolerant healthy nonhabitual milk consumers [NHMCs] reporting GID after consuming cow milk compared to 20 habitual milk consumers [HMCs] without GID. NHMCs and HMCs participated in a milk-load (250 mL) test, underwent blood sample collection at 6 time points over 6 h after milk consumption and collected urine samples and GID self-reports over 24 h. We measured the concentrations of 31 milk-derived bioactive peptides (BAPs), 20 amino acids, 4 hormones, 5 endocannabinoid system mediators, glucose and the dipeptidyl peptidase-IV (DPPIV) activity in blood and indoxyl sulfate in urine samples. Subjects also participated in a gut permeability test and delivered feces sample for gut microbiome analysis. Results showed that, compared to HMCs, milk consumption in NHMCs, along with GID, elicited a slower and lower increase in circulating BAPs, lower responses of ghrelin, insulin, and anandamide, a higher glucose response and serum DPPIV activity. The gut permeability of the two groups was similar, while the habitual diet, which was lower in dairy products and higher in the dietary-fibre-to-protein ratio in NHMCs, possibly shaped the gut microbiome; NHMCs exhibited lower abundance of Bifidobacteria, higher abundance of Prevotella and lower abundance of protease-coding genes, which may have reduced protein digestion, as evidenced by lower urinary excretion of indoxyl sulfate. In conclusion, the findings showed that a less efficient digestion of milk proteins, supported by a lower proteolytic capability of the gut microbiome, may explain GID in healthy people after milk consumption.